Top 10 plant pathogenic bacteria in molecular plant pathology - MANSFIELD, JOHN; GENIN, STEPHANE; MAGORI, SHIMPEI; CITOVSKY, VITALY; SRIARIYANUM, MALINEE; RONALD, PAMELA; DOW, MAX; VERDIER, VALÉRIE; BEER, STEVEN V.; MACHADO, MARCOS A.; TOTH, IAN; SALMOND, GEORGE; et al. (Molecular plant pathology, 2012)
SUMMARY Many plant bacteriologists, if not all, feel that their particular microbe should appear in any list of the most important bacterial plant pathogens. However, to our knowledge, no such list exists. The aim of this review was to survey all bacterial pathologists with an association with the journal Molecular Plant Pathology and ask them to nominate the bacterial pathogens they would place in a ‘Top 10’ based on scientific/economic importance. The survey generated 458 votes from the international community, and allowed the construction of a Top 10 bacterial plant pathogen list. The list includes, in rank order: (1) Pseudomonas syringae pathovars; (2) Ralstonia solanacearum; (3) Agrobacterium tumefaciens; (4) Xanthomonas oryzae pv. oryzae; (5) Xanthomonas campestris pathovars; (6) Xanthomonas axonopodis pathovars; (7) Erwinia amylovora; (8) Xylella fastidiosa; (9) Dickeya (dadantii and solani); (10) Pectobacterium carotovorum (and Pectobacterium atrosepticum). Bacteria garnering honourable mentions for just missing out on the Top 10 include Clavibacter michiganensis (michiganensis and sepedonicus), Pseudomonas savastanoi and Candidatus Liberibacter asiaticus. This review article presents a short section on each bacterium in the Top 10 list and its importance, with the intention of initiating discussion and debate amongst the plant bacteriology community, as well as laying down a benchmark. It will be interesting to see, in future years, how perceptions change and which bacterial pathogens enter and leave the Top 10.